Potential specific therapies in COVID-19. (May 2020) - Gul, Muhammad Hamdan; Htun, Zin Mar; Shaukat, Nauman; Imran, Muhammad; Khan, Ahmad
COVID-19 has grown into a global pandemic that has strained healthcare throughout the world. There is a sense of urgency in finding a cure for this deadly virus. In this study, we reviewed the empiric options used in common practice for COVID-19, based on the literature available online, with an emphasis on human experiences with these treatments on severe acute respiratory syndrome-associated coronavirus (SARS-COV-1) and other viruses. Convalescent blood products are the most promising potential treatment for use in COVID-19. The use of chloroquine or hydroxychloroquine (HCQ), remdesivir, and tocilizumab are some of the other promising potential therapies; however, they are yet to be tested in randomized clinical trials (RCTs). The use of lopinavir-ritonavir did not prove beneficial in a large RCT. The use of corticosteroids should be avoided in COVID-19 pneumonia unless used for other indications, based on the suggestion of harm in patients with SARS-COV-1 and Middle Eastern Respiratory Syndrome (MERS) infection. The reviews of this paper are available via the supplemental material section.